Dysregulation of leukocyte trafficking in ageing: Causal factors and possible corrective therapies. (January 2021) - Hopkin, S.; Lord, J.M.; Chimen, M.
Graphical abstract: Abstract: Ageing is a universal biological phenomenon that is accompanied by the development of chronic, low-grade inflammation and remodelling of the immune system resulting in compromised immune function. In this review, we explore how the trafficking of innate and adaptive immune cells under homeostatic and inflammatory conditions is dysregulated in ageing. We particularly highlight the age-related changes in the expression of adhesion molecules and chemokine receptor/ligands, and the accumulation of senescent cells that drive modulated leukocyte trafficking. These age-related changes to leukocyte trafficking are multifactorial and specific to leukocyte subset, tissue, type of vascular bed, and inflammatory status. However, dysregulated leukocyte trafficking ultimately affects immune responses in older adults. We therefore go on to discuss approved drugs, including anti-integrins, anti-chemokines and statins, as well as novel therapeutics that may be used to target dysregulated leukocyte trafficking in ageing, improve immune responses and delay the onset of age-related diseases.